Pengaruh Gaya Kepemimpinan, Motivasi, dan Pengembangan SDM terhadap Kinerja Karyawan - Fedri Zuwely; Ribhan Ribhan; Nova Mardiana (Jurnal Ilmiah ESAI, 2020)
The purpose of this study was to determine the effect of leadership style, motivation, and human resource development on employee performance implemented by PT KAI (Persero) Bandung 2 daop operating unit in influencing the performance of its employees. This study was analyzed using multiple linear regression analysis. The data used in this study used questionnaire data obtained from 236 respondents' answers to employees of PT KAI (Persero) Bandung 2 daop operation unit. The conclusion is that this study supports the proposed hypothesis, namely: Leadership style has a positive effect on employee performance, motivation has a positive effect on employee performance, and HR development has a positive effect on employee performance. Suggestions given from this research are PT KAI (Persero) Bandung Daop 2 operating unit so that in creating good employee performance every leader must have the care, trust, and motivation of employees actively working, entering on time and working seriously. The leader motivates the morning briefing / apple before work so that it is directed and controlled to do the task of carrying out the train journey. In improving human resource development, it is necessary to supervise the quality of work by increasing the training of employees who have not done special training, motivating employees to improve the formalities of higher education so that they can develop and have performance standards both in the company and the government.